2009
DOI: 10.1007/s10620-009-0960-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Adverse Clinical Outcomes with Concomitant Use of Clopidogrel and Proton Pump Inhibitors Following Percutaneous Coronary Intervention

Abstract: Concomitant use of clopidogrel and PPI in post-PCI patients is associated with a higher risk of MACE. This suggests that PPIs may attenuate clopidogrel's beneficial antiplatelet effect, which is crucial after PCI. Prospective randomized studies are warranted to provide definitive evidence for this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 11 publications
5
52
1
1
Order By: Relevance
“…11,12 Although a reduction in platelet inhibition would be expected to manifest as a reduction in the clinical efficacy of clopidogrel therapy, recent clinical outcome studies have reported conflicting results. Several small studies [13][14][15] and retrospective analyses of 3 larger population-based studies 16 -18 8,19,20 In light of these conflicting results from controlled clinical trials, further large-scale investigation into the real-world efficacy of PPI and clopidogrel combination therapy is required.…”
Section: Editorial See P 468 Clinical Perspective On P 482mentioning
confidence: 99%
See 3 more Smart Citations
“…11,12 Although a reduction in platelet inhibition would be expected to manifest as a reduction in the clinical efficacy of clopidogrel therapy, recent clinical outcome studies have reported conflicting results. Several small studies [13][14][15] and retrospective analyses of 3 larger population-based studies 16 -18 8,19,20 In light of these conflicting results from controlled clinical trials, further large-scale investigation into the real-world efficacy of PPI and clopidogrel combination therapy is required.…”
Section: Editorial See P 468 Clinical Perspective On P 482mentioning
confidence: 99%
“…26 In contrast, some previous retrospective analyses have shown an increase in cardiovascular events with coadministration of PPIs and clopidogrel. [15][16][17] These retrospective studies differ from the pivotal clinical trial analyses detailed above (TRITON-TIMI 38 and PLATO), with greater population heterogeneity, less control of assessments, and no consideration of the effects of CYP2C19 polymorphisms. The Juurlink et al 16 study was a nested, case-control study in Ontario residents Ն66 years of age.…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Yasuda et al (22) have previously demonstrated that combination therapy with DAPT and PPI decreases the effect of DAPT; however, the combination therapy was shown to decrease the risk of recurrent hemorrhage. Moreover, previous studies (23)(24)(25)(26) have also demonstrated that combination therapy with PPI and clopidogrel reduced the antiplatelet effect of clopidogrel. Therefore, whether combination therapy with clopidogrel and PPI is reasonable remains controversial, and further clinical trials are required.…”
Section: Discussionmentioning
confidence: 90%